Răspuns :
(2√3-3√2)*(3√3+2√2)=
=(2×3×√3×√3)+(2×2×√3×√3)-3×3×√2×√3-3×2×√2×√2
=6×(√3)²+4×(√3)²-9×√2×√3-6×(√2)²
=6×3+4×3-9√6-6×2
=18-12-9√6-12
=18-24-9√6
=-6-9√6
=-3(2+3√6)
=(2×3×√3×√3)+(2×2×√3×√3)-3×3×√2×√3-3×2×√2×√2
=6×(√3)²+4×(√3)²-9×√2×√3-6×(√2)²
=6×3+4×3-9√6-6×2
=18-12-9√6-12
=18-24-9√6
=-6-9√6
=-3(2+3√6)
(2√3-3√2)*(3√3+2√2)=
=(2×3×√3×√3)+(2×2×√3×√3)-3×3×√2×√3-3×2×√2×√2
=6×(√3)²+4×(√3)²-9×√2×√3-6×(√2)²
=6×3+4×3-9√6-6×2
=18-12-9√6-12
=18-24-9√6
=-6-9√6
=-3(2+3√6)
=(2×3×√3×√3)+(2×2×√3×√3)-3×3×√2×√3-3×2×√2×√2
=6×(√3)²+4×(√3)²-9×√2×√3-6×(√2)²
=6×3+4×3-9√6-6×2
=18-12-9√6-12
=18-24-9√6
=-6-9√6
=-3(2+3√6)